Effect of a simple core muscle training program on trunk muscle strength and neuromuscular control among pediatric soccer players - Kumahara, Ryotaro (J Exp Orthop, 2021)
PURPOSE: The purpose of this study was to examine the effect of simple core muscle training (CMT) program on trunk muscle strength and neuromuscular control among pediatric athletes. METHODS: Forty-nine male soccer players (mean age, 10.8 years) participated. The CMT program had three components (bench, side bench, and Nordic hamstrings) and was performed at least three times weekly for a year. Trunk flexion/extension muscle strength and the K/H ratio (determined by dividing knee separation distance by hip separation distance during drop-jump test and used as an index of lower limb valgus alignment) were measured, and the Y balance test (YBT) was performed before and after intervention. This study did not include the pure control group among the same team. To consider the effect of CMT on trunk muscle strength due to physical growth, we used the data of trunk muscle strength from the local cohort study previously conducted in our institution. One hundred participants who matched the age, height, body weight, and body mass index of the training group was designated as a control group. RESULTS: In the training group, the trunk flexion/extension strength significantly increased at 6 months (p < 0.001, p < 0.001, respectively) and 12 months (p < 0.001, p < 0.001, respectively) compared to initial value. The K/H ratio at initial contact and maximum knee flexion phase significantly increased at 6 months (p < 0.001 and p < 0.001, respectively); however, it did not increase at 12 months (p = 0.384 and p = 0.070, respectively) compared to the initial value. In the YBT, the maximized reach distance in each direction significantly increased after intervention on both the dominant and non-dominant sides, except in the posteromedial direction on the non-dominant foot. Compared to the control group, although there was no significant difference in trunk flexion/extension strength at baseline (p = 0.141 and p = 0.390, respectively), the training group showed significantly higher trunk flexion/extension muscle strength at 12 months (p < 0.001 and p < 0.001, respectively). CONCLUSION: The CMT program increased trunk muscle strength and improved dynamic balance among pediatric male athletes. LEVEL OF EVIDENCE: Level II